PENGELOLAAN IKLIM SEKOLAH YANG KONDUSIF UNTUK KERJA GURU (Studi Kasus SMA Negeri 1 Prambanan Klaten) - Purwanta, Sri (2011)
This research is describing (1) teacher work relation character in SMA Negeri 1 Prambanan, and (2) school layout character in SMA Negeri 1 Prambanan. It has done in SMA Negeri 1 Prambanan, with qualitative research. Analysis technique used in research is site analysis. Research results are (1) teacher teamwork relation can be devided into teamwork to student, teamwork to parents and society, teamwork to headmaster, and teamwork to colegue in teamwork relation framework to reach education purposes. Teacher and student teamwork is as an effort to create fun situation for student, executes to students fairly, achievement giving, guiding in extracurricular, both in formal or informal situation. Teamwork relation to parent reflects on routine meeting, discussion schedule, telling student achievement and work result, giving assignment for student to do parent interview. Teamwork to headmaster is in planning, organizationing, briefing, coordinating, funding and assessing curriculum activity, learner, medium and infrastructure, personalia, and school finances. Teacher teamwork relation with other teachers, executes to create and maintain teacher relation both base on work environemnt or in entire relationship, mutual opinion and information exchange, giving advice mutually and helping each other, both for private need or to execute their profession duty. In maintaining, guiding and improving teacher professional organization as medium dedication. (2) classroom layout in SMA Negeri 1 Prambanan has arranged according to each function, each rooms completed with needed tools and equipment. Classroom layout purposes to create comfort work environment, and guarantee school activity execution to reach exist purposes with consider to all classrom utilization and working pleasure. Table- chair arrangement in classroom enable students to interact and movement mobility to do learning activity. Student seat position changes everytime so student interaction in class will be better and raise socialization each other and also discover student boredom with exist seat.